A Study on the Influence of Higher Education Foreign Language Teachers’ Intercultural Communication Competence on the Dissemination of Chinese Excellent Culture - Wei, Xinyu (Applied mathematics and nonlinear sciences, 2024)
This study employs gray system theory to refine the multiple linear regression model, resulting in the development of the gray multiple linear regression method. Utilizing School A as the primary subject, this approach involves gray scaling the intercultural communication skills of college instructors (independent variable) and the effectiveness of Chinese culture dissemination (dependent variable). This transformation aids in resolving the sequence of whitened background values for each variable. This transformation aids in sequencing the whitened background values for each variable. The regression coefficients are then calculated using the Cholesky method to determine the linear correlation between the variables and assess how intercultural communication skills influence cultural dissemination outcomes. The analysis of the influence of college teachers’ intercultural communicative competence on the effect of cultural transmission found that the language competence of college foreign language teachers is related to “attitude toward learning Chinese excellent culture” (0.432) and “whether it is necessary to teach the idea of Chinese excellent culture in the classroom” (0.503) both have significant correlations. The analytical results of this paper provide a reference basis for promoting the wide dissemination of Chinese excellent culture, as well as a direction for improving the cross-cultural communicative competence of foreign language teachers in colleges and universities.